Analisis Kualitas Pelayanan E-Procurement pada Pengadaan Barang dan Jasa di Kota Semarang - Pratiwi, Riyan Rahayu; Widowati, Nina; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research aims to analize of service quality of e-procurement ini the procurement of good and services ini Semarang city and to know the aspects that drive and inhibit the quality of e-procurement services in Semarang city. Locus if this research is Sekretaris Daerah Kota Semarang Bagian Pembangunan who became chief executive of Layanan Penyediaan Secara Elektronik (LPSE) and providers of goods and services in Semarang City. This research used qualitative research methods explorative. Subjects in this research consisted of five key informants.Based on the results of the research showed that the service quality of e-procurement in Semarang City has not been optimally. Although there are several dimensions of service quality are considered have optimal. Factors that impede service quality of e-procurement which aspects of several dimensions have not been optimally. Need for improvement and optimization of various dimensions of service quality of service that is increasing.